Military forces and COVID-19 as smokescreens for Amazon destruction and violation of indigenous rights - Ferrante, Lucas; Fearnside, Philip Martin (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
The President of Brazil has adopted an anti-environmental stance since taking office in January 2019, weakening the rights of indigenous peoples and environmental legislation and militarizing the environmental and indigenous agencies. The president’s stance on the COVID-19 pandemic gives priority to economic development rather than to saving lives. The administration’s environment minister even suggested taking advantage of the media’s attention being focussed on the pandemic as an ‘opportunity’ to weaken environmental legislation. Here we argue that both the pandemic and the militarization of Brazil’s environmental protection have served as smokescreens to weaken environmental protections, and have also put Brazil’s indigenous peoples at risk and violated their rights.